DEVELOPMENT OF A LEARNING MODEL FOR READING NEWS TEXTS BASED ON SEVIMA EDLINK CLASS VIII JUNIOR HIGH SCHOOL STUDENTS - Fina Sabirah Radwa; Fathiaty Murtadho; Reni Nur Eriyani (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
This study aims to discover the development of a learning model for reading news texts in Indonesia. This research uses Research and Development method based on the ADDIE model which has developed by Branch. The analysis stage, curriculum, learning models, and news text materials were conducted. Design stage, namely introduction, Basic Competencies, learning objectives, determining news elements, summarizing & concluding news, the structure and linguistic rules of news texts, and conveying information in the form of news. The development stage is a step to develop a learning model for reading news text based on Sevima Edlink by applying the frameworks of the designated product. The implementation stage requires validation from the experts, media, and Indonesian language teachers. The testing phase on class VIII students in two Bekasi city schools with 40 students. The results of the product trial instrument for students, 19.8% of the 20 students of school A and 19.6% of the 20 students of school B answered accordingly. Based on the results of the stages above, the development of a learning model for reading news texts based on Sevima Edlink is compatible with the ADDIE model.